The insider threat : a Pike Logan thriller - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2015)
The United States has anticipated and averted countless attacks from terrorist groups--thanks in large part to the extralegal counterterrorist unit known as the Taskforce. But in The Insider Threat, a much more insidious evil is about to shatter the false sense of safety surrounding civilized nations. While world powers combat ISIS on the battlefield, a different threat is set in motion by the group--one that can't be defeated by an airstrike. Off the radar of every Western intelligence organization, able to penetrate America or any European state, they intend to commit an act of unimaginable barbarity. Only Pike Logan and the Taskforce stand in the way of an attack no one anticipates, a grand deception that will wreak unthinkable chaos and reverberate throughout the Western world.